2003
DOI: 10.1071/ah030088
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based clinical practice in falls prevention: a randomised controlled trial of a falls prevention service

Abstract: Aims (OR=12.3;. We were unable to show a reduction in falls (OR=1.7;. Conclusions:A patient centered evidence-based approach is feasible and effective in increasing uptake of falls prevention advice. Long term compliance with advice needs further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 22 publications
5
32
0
9
Order By: Relevance
“…Previous studies have found that education during inpatient stays about patients' personal risk factors and fall prevention strategies increases the likelihood of these same patients engaging in fall prevention behaviors both during their hospitalization and postdischarge. [21][22][23] This information combined with our data suggests that the inpatient…”
Section: Schmid Scores Of Patients Who Fell Systemwidesupporting
confidence: 67%
“…Previous studies have found that education during inpatient stays about patients' personal risk factors and fall prevention strategies increases the likelihood of these same patients engaging in fall prevention behaviors both during their hospitalization and postdischarge. [21][22][23] This information combined with our data suggests that the inpatient…”
Section: Schmid Scores Of Patients Who Fell Systemwidesupporting
confidence: 67%
“…Two studies that tested multifactorial interventions found a statistical and clinical benefit. 6 7 Two others, one relying on referral to health professionals, 8 and the other on education and advice, 9 found no effect, which is consistent with previous meta-analyses of multifactorial community interventions. 10 Logan and colleagues give limited detail on the intervention except that it was based on the 2004 clinical practice guidelines for prevention of falls from the UK National Institute for Health and Clinical Excellence (NICE).…”
supporting
confidence: 71%
“…[30][31][32][33][34][35][36][37][38] Of these studies, Banez et al (2008) 30 and McQueen (2003) 34 provided an intensive patient education programme where a face-to-face hourly group education session was conducted over eight or more weeks. The remaining studies provided brief advice or instructions; for example, home safety tips in which the duration of education was unknown or less than 20 minutes.…”
Section: Studies Of Post-hospitalized Older Adults (Multifactorial Famentioning
confidence: 99%